PENDAMPINGAN PEMBUATAN BRIKET TONGKOL JAGUNG SEBAGAI ENERGI ALTERNATIF UNTUK PETANI DI DESA TETEY - Aritonang, Henry Fonda; Wuntu, Audy Denny; Pasau, Guntur (Universitas Padjadjaran, 2025)
Every year, the amount of corn cob waste continues to increase. In Tetey Village, Dimembe District, North Minahasa Regency, North Sulawesi Province, corn cobs are considered to have no significant economic value by the community and are generally only used as animal feed. To address this issue, efforts were made to process corn cob waste into briquettes—an alternative energy source produced from carbon-based materials through a high-temperature pyrolysis process. The utilization of corn cob waste aimed to reduce waste while simultaneously boosting the economy of the people in Tetey Village. This activity was carried out through training and assistance in making briquettes from corn cobs. The preparation and coordination phase involved discussions on training materials and checking the availability of corn cobs in Tetey Village. In the implementation phase, the formulation of corn cob briquettes was analyzed to ensure it met the standards, along with the provision of training materials regarding the manufacturing process. The monitoring and evaluation phase involved measuring the partners' understanding of briquette making before and after the training, as well as analyzing the briquette formulation tested in the laboratory. The results of the assistance showed an increase of more than 60% in the partners' understanding of corn cob briquette production after receiving training. The briquette formulation test showed that using 72% water (v/b from the mass of corn cobs) and 10% tapioca flour (b/b from the mass of corn cobs) could be recommended for the development of corn cob charcoal briquette production by the partners. Setiap tahun, jumlah limbah tongkol jagung terus bertambah. Di Desa Tetey, Kecamatan Dimembe, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara, tongkol jagung dianggap tidak memiliki nilai ekonomi yang signifikan oleh masyarakat, sehingga umumnya hanya dimanfaatkan sebagai pakan ternak. Untuk mengatasi permasalahan tersebut, dilakukan upaya pengolahan limbah tongkol jagung menjadi briket. Briket merupakan sumber energi alternatif yang dihasilkan dari bahan berkarbon melalui proses pirolisis pada suhu tinggi. Pemanfaatan limbah tongkol jagung bertujuan untuk mengurangi limbah yang terbuang percuma sekaligus meningkatkan perekonomian masyarakat Desa Tetey. Kegiatan ini dilaksanakan melalui pelatihan dan pendampingan dalam pembuatan briket dari tongkol jagung. Tahap persiapan dan koordinasi dilakukan melalui diskusi mengenai materi pelatihan serta pengecekan ketersediaan tongkol jagung di Desa Tetey. Pada tahap implementasi, dilakukan analisis formulasi briket tongkol jagung untuk memastikan sesuai dengan standar, serta pemberian materi pelatihan mengenai proses pembuatannya. Tahap monitoring dan evaluasi melibatkan pengukuran pemahaman mitra tentang pembuatan briket sebelum dan sesudah pelatihan, serta analisis formulasi briket yang diuji di laboratorium. Hasil pendampingan menunjukkan peningkatan pemahaman mitra hingga lebih dari 60% mengenai pembuatan briket tongkol jagung setelah menerima pembekalan. Uji formulasi briket arang menunjukkan bahwa penggunaan air sebesar 72% (v/b dari massa tongkol jagung) dan tepung tapioka 10% (b/b dari massa tongkol jagung) dapat dijadikan rekomendasi untuk pengembangan produksi briket arang tongkol jagung oleh mitra.